Analisis Hubungan Stres Kerja dengan Kecelakaan Kerja pada Pekerja Konstruksi Proyek Pembangunan Jalan Tol Yogyakarta – Bawen Paket 1 (Seksi 1) Tahun 2023 - Rachmat, Shafira Agustina; Ramdhan, Doni Hikmat Hikmat (National Journal of Occupational Health and Safety, 2023)
Construction workers are a job with high level of risk. There are many cases of construction workers experiencing stress due to their work, even until accident occurs. Factors that contribute to the occurrence of work stress include physical hazards and psychosocial factors, but it does not rule out the possibility of influence from individual characteristics. This study aims to analyze the correlation between occupational stress and workplace accidents in construction workers at Yogyakarta – Bawen Toll Road Construction Project Package 1 (Section 1) in 2023. This research is a quantitative study with a cross-sectional study design. The factors studied included work stress levels, physical hazards in the form of work climate, psychosocial factors which were job content (task design, workload, and work schedule) and job context (role in the organization, interpersonal relationships, and job satisfaction), as well as individual characteristics that are associated with the occurrence of work accidents. A total of 260 construction workers were participated in this study. The results showed that 234 construction workers (90%) experienced moderate levels of stress and 154 workers (59.2%) experienced work accidents. A relationship was found between occupational stress and workplace accidents. Based on the results obtained, it is necessary to control the exposure to occupational stress and its factors at Yogyakarta – Bawen Toll Road Construction development project to minimize the occurrence of stress on workers and workplace accidents.